Three F-actin assembly centers regulate organelle inheritance, cell-cell communication and motility in Toxoplasma gondii - Nicolò Tosetti; Nicolas Dos Santos Pacheco; Dominique Soldati-Favre; Damien Jacot (eLife, 2019)
Toxoplasma gondii possesses a limited set of actin-regulatory proteins and relies on only three formins (FRMs) to nucleate and polymerize actin. We combined filamentous actin (F-actin) chromobodies with gene disruption to assign specific populations of actin filaments to individual formins. FRM2 localizes to the apical juxtanuclear region and participates in apicoplast inheritance. Restricted to the residual body, FRM3 maintains the intravacuolar cell-cell communication. Conoidal FRM1 initiates a flux of F-actin crucial for motility, invasion and egress. This flux depends on myosins A and H and is controlled by phosphorylation via PKG (protein kinase G) and CDPK1 (calcium-dependent protein kinase 1) and by methylation via AKMT (apical lysine methyltransferase). This flux is independent of microneme secretion and persists in the absence of the glideosome-associated connector (GAC). This study offers a coherent model of the key players controlling actin polymerization, stressing the importance of well-timed post-translational modifications to power parasite motility.